Integrasi Artificial Intelligence dalam Asesmen dan Pembelajaran Anak Usia Dini: A Systematic Literature Review - Najwa Azizah Ramadhani; Roby Naufal Arzaqi; Namira Tri Mareta; Ghea Alza Jazilia (JEA (Jurnal Edukasi AUD), 2026)
This study aims to analyse and synthesise the use of Artificial Intelligence (AI) in learning, assessment, and social-emotional development in early childhood education. The method employed was a Systematic Literature Review (SLR) in accordance with the PRISMA guidelines. Data were obtained from the Scopus AI/Scopus database, covering publications from 2015 to 2025. Following a selection and quality assessment process, 10 articles suitable for analysis were identified. The findings indicate that AI plays a role in three main aspects: as an adaptive learning medium that supports children’s engagement, motivation, literacy, and skills; as a data-driven assessment tool for analysing development and personalising learning; and as a medium for early stimulation in children’s social-emotional development. The implementation of AI is also linked to teachers’ competence readiness, infrastructure support, data security, and child-friendly technology design. These findings emphasise that AI needs to be integrated within a pedagogical framework aligned with child development principles. AI has the potential to be an effective tool for supporting learning and assessment, yet it still requires careful management to ensure it does not replace direct interaction in early childhood education.